Evaluating participatory research: Framework, methods and implementation results. (1st July 2015) - Smajgl, Alex; Ward, John
Abstract: This paper describes a structured participatory process and associated evaluation protocol developed to detect systems learning by decision makers involved in the management of natural resources. A series of facilitated participatory workshops were conducted to investigate learning when decision makers and influencers were confronted with the multiple, complex interactions arising from decisions concerned with the nexus of water, food and energy security. The participatory process and evaluation of learning were trialled in the Greater Mekong Subregion (GMS), where integrated scientific evidence was systematically presented to challenge existing beliefs concerned with the effectiveness of proposed policy actions and development investments. Consistent with theoretical propositions, individually held values, beliefs and attitudes were deployed as the primary factors (and psychometrics) that underpin and influence environmental management decision making. Observed and statistically significant changes in the three psychometrics expressed by decision makers in response to the facilitated presentation of scientific evidence during the participatory process, provided supportive evidence of systems learning and the evaluation protocol. Highlights: This paper conceptualises an innovative protocol for monitoring and evaluating participatory social science research processes. Thereby we provide effective (quantitative) diagnostics for understanding how science impacts on existing knowledge systems. In contrast to other available evaluation protocols or frameworks we developed an ex-ante approach. Results are presented for an implementation of this protocol in the Mekong region.